Citizens of Europe? - Bruter, M. author. aut Link
XVI, 221 p.
Keywords: This book shows empirically for the first time how a mass European identity has emerged across the EU member states between 1970 and the present day. Beyond this novel approach, it also offers a whole new theory of political identities, based on two 'civic' and 'cultural' components. Michael Bruter shows how multiple identities reinforce - rather than exclude - each other, and studies in depth the unsuspected impact of the media and political institutions on the emergence of new political identities.